Extraction of essential oils from jasmine flower using supercritical co2 co-solvent extraction - Norulshahida, Che Din (2006)
Pure essential oils are derived from various part of the plant. These essential oils have a very high commercial value due to its properties. They are widely used in the various fields of industries, such as perfumery industries and pharmaceuticals. Conventional technique to extracts this oil such as steam distillation is unsuitable since it induce thermal degradation of compounds in the oils. It is for this reason that the extraction of essential oils using supercritical fluid extraction method is said to be the most effective method. It also can avoid contamination of the oil. This extraction technique employed carbon dioxide (CO2) as solvent due to CO2 is stateless, odorless, non-toxic and chemical inertness and would not contaminate the environment and products. Thus, the material residues can be used without pretreatment. Beside that, the low critical properties make CO2 the most preferable solvent in this technique. The used of co-solvent also affect the extraction of these essential oils because it could modify the CO2 selectivity towards the fragrances compound. This can in turn produce higher quantity of products. For this purpose, two co-solvent had been employed, viz. ethanol and methanol.